2022
DOI: 10.1037/rev0000228
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance as forbearance: Overcoming intuitive versus deliberative objections to cultural, religious, and ideological differences.

Abstract: Tolerance is widely considered to be a key response to the challenge of managing diversity in pluralistic societies. However, tolerance comes in a number of different forms with distinct psychological profiles and societal implications. Drawing on research from political science, philosophy, sociology, and several subdisciplines within psychology, we discuss tolerance as a process of forbearance, which has received little attention in psychology. We propose a dual-process model of moral reasoning to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 209 publications
1
19
0
2
Order By: Relevance
“…While Study 1 found, consistent with previous research (Cole Wright et al, 2008;Skitka et al, 2005), that moralization plays an on the level of dissent of the target behaviours. These findings provide supporting evidence for the proposed weighing process of toleration (Forst, 2013;Verkuyten et al, 2021), as well as advancing the research on moralization and the complex role it plays in intergroup relations. Additionally, Study 4 demonstrated that emphasizing a particular moral value can even lead to higher tolerance of a practice that is considered highly dissenting and challenging for societal cohesion.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While Study 1 found, consistent with previous research (Cole Wright et al, 2008;Skitka et al, 2005), that moralization plays an on the level of dissent of the target behaviours. These findings provide supporting evidence for the proposed weighing process of toleration (Forst, 2013;Verkuyten et al, 2021), as well as advancing the research on moralization and the complex role it plays in intergroup relations. Additionally, Study 4 demonstrated that emphasizing a particular moral value can even lead to higher tolerance of a practice that is considered highly dissenting and challenging for societal cohesion.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, people's moral concerns about minority behaviours and their related tolerance do not simply reflect their prejudicial feelings. The current pattern of findings indicate that tolerance is not a global construct reflecting prejudicial attitudes (Verkuyten et al, 2021;, but depends on the particular behaviours that people are asked to tolerate and the extent to which these are considered normatively dissenting, and therefore, raise various moral concerns.…”
Section: Discussionmentioning
confidence: 78%
“…It is around such concrete debates about differences that ways of life collide and questions emerge about what beliefs, practices, and norms people are willing to tolerate in society. Tolerance in the classical sense of forbearance and putting up with beliefs and lifestyles one disapproves of is considered a critical and necessary condition for “diversity and equality among people living in peace” (Vogt, 1997, p. 5; see also Cohen, 2004; Verkuyten et al, 2021).…”
Section: Tolerance and Dual-process Thinkingmentioning
confidence: 99%
“…Research finds that individuals can change their minds about a moral question when they are asked to reflect on it (Paxton et al, 2012), that deliberative thinking can lead to less emotion-based moral judgments (Pennycook et al, 2015), that adopting a mindful orientation can lead to higher acceptance (Baumgartner & Morgan, 2019), and that considered thoughtful and relevant arguments lead to increased acceptance (Petersen et al, 2010; Sniderman et al, 1989). Therefore, it has been argued theoretically that tolerance is more likely when people engage in deliberative thinking in which they consider reasons for condoning what they disagree with, disapprove of, or object to (Verkuyten et al, 2021). However, to our knowledge, there is no experimental evidence that deliberative thinking does indeed lead to tolerance.…”
Section: Tolerance and Dual-process Thinkingmentioning
confidence: 99%
“…Theories of intergroup toleration differentiate between attitudes towards the cultural practices of another group, and attitudes towards people belonging to another group (Verkuyten, Adelman, et al, 2021). People may feel negatively towards a group's cultural practices and impose restrictions without devaluing the group as whole; or conversely people may derogate members of another group without trying to restrict them.…”
Section: Defining What Collective Autonomy Restriction Is (And Is Not)mentioning
confidence: 99%